The Effectiveness of PQ4R Learning Method in Ecosystem Materials To Improve Students’ Learning Outcomes and Reading Skills (Journal of Innovative Science Education, 2020)
This study aims to analyze the effectiveness of the PQ4R learning method on learning outcomes of students' knowledge and reading skills. The design in this study used posttest only control group with 2 classes taking techniques. Class X-1 as a control class and X-2 as an experimental class using the PQ4R learning method. Data analysis techniques used descriptive analysis to determine the completeness of the learning outcomes of the experimental class. Test the improvement of student learning outcomes with N-gain values. Comparative hypothesis testing with paired t-test samples and reading skills with a questionnaire and observation. The results of students' mastery learning showed that only 10 students out of 35 students reached KKM. Tests for improving student learning outcomes indicate a medium category. The comparative hypothesis test shows the asymp.sig value of 0.001, which means that there are differences in the learning outcomes of the control class and the experimental class. And students' reading skills show the distribution of questionnaires that agree and the observation sheets are categorized as good. The conclusion of this study is that the PQ4R learning method is better than the class that does not use the PQ4R learning method on student learning outcomes and reading skills on ecosystem material.